Adipose-Derived Mesenchymal Stem Cells From a Hypoxic Culture Improve Neuronal Differentiation and Nerve Repair - Wu, Szu-Hsien; Liao, Yu-Ting; Hsueh, Kuang-Kai; Huang, Hui-Kuang; Chen, Tung-Ming; Chiang, En-Rung; Hsu, Shan-hui; Tseng, Ting-Chen; Wang, Jung-Pan (Frontiers in Cell and Developmental Biology, 2021)
Hypoxic expansion has been demonstrated to enhance in vitro neuronal differentiation of bone-marrow derived mesenchymal stem cells (BMSCs). Whether adipose-derived mesenchymal stem cells (ADSCs) increase their neuronal differentiation potential following hypoxic expansion has been examined in the study. Real-time quantitative reverse transcription-polymerase chain reaction and immunofluorescence staining were employed to detect the expression of neuronal markers and compare the differentiation efficiency of hypoxic and normoxic ADSCs. A sciatic nerve injury animal model was used to analyze the gastrocnemius muscle weights as the outcomes of hypoxic and normoxic ADSC treatments, and sections of the regenerated nerve fibers taken from the conduits were analyzed by histological staining and immunohistochemical staining. Comparisons of the treatment effects of ADSCs and BMSCs following hypoxic expansion were also conducted in vitro and in vivo. Hypoxic expansion prior to the differentiation procedure promoted the expression of the neuronal markers in ADSC differentiated neuron-like cells. Moreover, the conduit connecting the sciatic nerve gap injected with hypoxic ADSCs showed the highest recovery rate of the gastrocnemius muscle weights in the animal model, suggesting a conceivable treatment for hypoxic ADSCs. The percentages of the regenerated myelinated fibers from the hypoxic ADSCs detected by toluidine blue staining and myelin basic protein (MBP) immunostaining were higher than those of the normoxic ones. On the other hand, hypoxic expansion increased the neuronal differentiation potential of ADSCs compared with that of the hypoxic BMSCs in vitro. The outcomes of animals treated with hypoxic ADSCs and hypoxic BMSCs showed similar results, confirming that hypoxic expansion enhances the neuronal differentiation potential of ADSCs in vitro and improves in vivo therapeutic potential.